Early exposure to general anesthesia impairs social and emotional development in rats - Diana, Paolo (Mol Neurobiol, 2019)
Several animal and emerging human studies suggest an association between an early exposure to general anesthesia (GA) and long-lasting problems with complex social and emotional behaviors such as inattentiveness, impulsivity, anxiogenic tendencies, as well as difficulties engaging in proper social intercourse, with significant increase in attention deficit and hyperactivity-type behaviors. To further investigate these behaviors, and to examine the potential of presently available rodent behavioral models to guide future assessments of long-term socio-emotional impairments in humans, we examined the long-term effects of GA on anxiety/fear and social behaviors. We exposed male and female Sprague-Dawley infant rats at the peak of their synaptogenesis to either GA containing midazolam (9 mg/kg, i.p.), 70% nitrous oxide (N(2)O) and 0.75% isoflurane (Iso) administered in 29–30% oxygen [experimental] or air (with 30% oxygen) plus the vehicle, 0.1% dimethyl sulfoxide [Sham] for 6 hrs. Behavioral experiments were conducted at adolescence (the open-field test) and young adulthood (the open-field test, the elevated plus-maze and the social novelty test). We report that an early exposure to GA during critical stages of brain development results in long-lasting increase in risk-taking tendencies and significant changes in the anxiety-related behaviors when tested in young adult rats. In addition, we noted novelty-seeking tendencies/less guarded behavior with changes in social discrimination. We conclude that early exposure to anesthesia may have lasting influences on emotional and social development. Importantly, our results show that currently used rodent behavioral models could be a good correlate to assess long-term socio-emotional GA-induced impairments observed in humans.